Effects of Visual Display Unit on Ocular Accommodation in Young Adults - Vishal Biswas; Roshni Majumder (British and Irish Orthoptic Journal)
Purpose: To evaluate the impact of gaming on ocular accommodative parameters. Methods: A comparative and experimental study was conducted among non-orthoptic university students for a duration of six months from September 2023 to March 2024. After a half-hour of gaming, the subjects’ accommodative parameters were examined and compared. The accommodative parameters before and after iPad gaming were compared. Results: The study included 80 participants (mean age 22.96 ± 2.23 years; 50 males, 30 females). Post gaming near-point of accommodation decreased (right eye: 10.75D to 7.15D, p < 0.001), Negative Relative Accommodation (NRA) increased from 2.64 ± 0.23 DS to 2.92 ± 0.37 DS, whereas Positive Relative Accommodation (PRA) decreased from –2.46 ± 0.41 DS to –1.78 ± 0.31 DS. The Monocular Estimation Method (MEM) values showed accommodative lag (right eye: +0.46 ± 0.15 DS to +1.24 ± 0.26 DS, p < 0.001). Monocular Accommodative Facility (MAF) and Binocular Accommodative Facility (BAF) exhibited decrease in facility (MAF; right eye: 10.34 to 4.54 cpm, BAF: 10.65 to 4.90 cpm, p < 0.001). Conclusion: This study shows 30 minutes of gaming using digital devices leads to decrease in accommodative parameters, potentially causing ocular fatigue and binocular vision anomalies in young individuals.